Agrochemical-induced carcinogenesis mechanisms: systematic review - Soares da Silva, Ruan Gabriel (2022)
Chronic exposure to pesticides and endocrine disruptors cause changes in gene expression in breast tissue, which makes women subjected to this condition more likely to develop breast cancer. This study aimed to systematically investigate and review the correlation between exposure to pesticides and breast carcinogenesis, pointing out mechanisms observed in vivo and in situ. The Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) protocol was used, the search was performed in PubMed, resulting in 58 articles included in the present study. Given the above, cellular genotoxicity mediated by exposure to pesticides of different chemical classes and endocrine disruptors can be observed, which in theory trigger genotoxic stress in normal breast tissue promoting carcinogenesis, and in those already diagnosed with breast cancer lead to greater probability to develop metastases. This review highlights the need for studies that explore and identify the mechanisms involved in such a condition, with unequivocal evidence linking breast carcinogenesis with exposure to chemical compounds and endocrine disruptors.